Deleterious effects of low level of vitamin E and high stocking density on the hematology response of pacus, during chronic inflammatory reaction - Andrade Belo, Marco Antonio de [UNESP]; Moraes, Flavio Ruas de [UNESP]; Yoshida, Luciana [UNESP]; Rosa Prado, Ed Johnny da [UNESP]; Engracia de Moraes, Julieta Rodini [UNESP]; Soares, Vando Edesio; Silva, Marta Gomes da (Elsevier B.V., 2014)
The effects of dietary supplementation with 12.6, 58.2 and 310.4 mg of vitamin E/kg dry diet on the hematology response of pacus (Piaractus mesopotamicus), submitted to different stocking densities (5 kg/m(3) and 20 kg/m(3)), were investigated during chronic inflammatory reaction. After a feeding period of 18 weeks, pacu juveniles were anesthetized for inserting round glass coverslips 13 mm in diameter into the subcutaneous connective tissue. 126 fish from 18 groups (i.e., seven fish per aquaria) were sampled for blood collection 2, 7 and 15 days post-implantation to determine levels of plasma cortisol, erythrocyte, thrombocyte and leucocyte counts. In the presence of chronic inflammation, pacus fed with 12.6 mg/kg of vitamin E and kept in high stocking density (20 kg/m(3)) resulted in increased number of circulating red blood cells and hematocrit percentage associated with microcytosis. Thrombocytosis and neutrophilia were observed in the acute phase of pacu defense response. However, it was found that a significant increase in monocyte counts and decrease in thrombocyte, neutrophil and lymphocyte counts in animals were maintained at high stocking density. Pacus fed with 12.6 mg of vitamin E/kg of dry diet presented low number of lymphocytes and LG-PAS+, and these animals showed elevated cortisol levels associated to low counts of monocytes. (C) 2013 Published by Elsevier B. V.
Keywords: Piaractus mesopotamicus; Tocopherols; Blood parameters; Cortisol; Chronic inflammation